2017
DOI: 10.1177/0266242617741534
|View full text |Cite
|
Sign up to set email alerts
|

Founding logics, technology validation, and the path to commercialization

Abstract: Considerable research has demonstrated that small- and medium-sized enterprises (SMEs) who obtain institutionalized third-party endorsements experience higher performance. In this study, we develop an important boundary condition around this process. Drawing on institutional logics, we introduce the novel concept of founding logics. We then develop and test a theory in which founding logics play a role in both an SME’s decision to seek a third-party endorsement for the firm’s technology and then the likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…Specifically, our findings support the view of legitimation work being subject to logic tensions also when these logics are well-aligned in terms of strategic options. In addition, our study responds to the call by Ciuchta et al (2018) for research that examines the origins of founding logics and its implications for new venture endorsement. Our findings highlight how variations in entrepreneur backgrounds translate into differences in founding logics, but also how the mobilisation of logics in the legitimation work of sustainability ventures leads to differences in partnership outcome.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Specifically, our findings support the view of legitimation work being subject to logic tensions also when these logics are well-aligned in terms of strategic options. In addition, our study responds to the call by Ciuchta et al (2018) for research that examines the origins of founding logics and its implications for new venture endorsement. Our findings highlight how variations in entrepreneur backgrounds translate into differences in founding logics, but also how the mobilisation of logics in the legitimation work of sustainability ventures leads to differences in partnership outcome.…”
Section: Discussionmentioning
confidence: 72%
“…Building upon the first stage of analysis, we proceeded to a more theoretically driven stage. Through an in-depth exploration of literature on sustainable entrepreneurship (O'Neil and Ucbasaran, 2016; York et al, 2016), new venture legitimation (Navis and Glynn, 2011; Uberbacher, 2014; Truong and Nagy, 2020), and hybrid organising and social enterprises (Pache and Santos, 2013; Ciuchta et al, 2018; Wagenschwanz and Grimes, 2021), we analysed whether the emerging themes suggested concepts that might help us to describe and explain the phenomena we observed. Building on insights from the relevant literature, the first-order codes were grouped into second-order themes through axial coding (Corbin and Strauss, 1990; Gioia et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…For scholars, the development of an academic career involves long-term academic training and socialization [20]. In the meantime, they have long been immersed in the normative system of advocating scientific spirit, adhering to the scientific logic of pursuing technological novelty [8,10], while entrepreneurship itself is a more commercialized activity and pursues business logic, involving a strong focus on financial outcomes, as well as attention on technology robustness and utility [21]. Therefore, there is a huge gap between the scholar role and entrepreneur role in terms of their values, beliefs, and norms.…”
Section: Lowmentioning
confidence: 99%
“…Therefore, there is a huge gap between the scholar role and entrepreneur role in terms of their values, beliefs, and norms. Substantial empirical evidence shows that these two types of logics persist over time [10,22]. For example, Mary and Giovanni [23] assert that scholars often use scientific logic to deal with commercialization problems when they are faced with identity transition.…”
Section: Lowmentioning
confidence: 99%
See 1 more Smart Citation